Resolving high potential structural deterioration in Ni-rich layered cathode materials for lithium-ion batteries operando. (January 2023) - Mikheenkova, Anastasiia; Gustafsson, Olof; Misiewicz, Casimir; Brant, William R.; Hahlin, Maria; Lacey, Matthew J.
Abstract: Lix Ni0.90 Co0.05 Al0.05 O2 (NCA) extracted from an automotive battery cell is studied using a combination of in-house operando techniques to understand the correlation between gas evolution and structural collapse when NCA is cycled to high potentials in a lithium-ion battery configuration. The operando techniques comprise X-ray diffraction (XRD) and online electrochemical mass spectrometry (OEMS), and cycled using intermittent current interruption (ICI). The ICI cycling protocol is used to assess the dynamic change in resistance as well as to provide a validation of the operando setups. Both gas evolution and structural collapse have previously been observed as degradation mechanisms of Ni-rich electrodes including NCA, however, their causal link is still under debate. Here our presented results show a correlation between the decrease of the interlayer distance in NCA with both an increase in CO2 evolution and diffusion resistance above 4.1 V. Additionally, particle cracking, which is a mechanism often correlated with gas evolution, was found to be reversible and visible before gas evolution and Li diffusion resistance increase. The ICI technique is shown to be useful for the correlation of operando experiments on parallel setups and evaluation of mass transport dependent processes. Graphical abstract: Highlights: Structural changes, mass transport resistance, and gas evolution are correlated. Oxygen evolution is not exclusively limited to the surface phase. Particle cracking was observed before increase of resistance and CO2 evolution.